Pengetahuan dan Respon Siswa Sekolah Dasar Terhadap Nyeri Setelah Pendidikan Kesehatan Teknik Relaksasi Pernapasan Dalam - Nuraini Hakim; Awalin, Fischa (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Tetanus and diphtheria that infect the children may cause emergency. Children with tetanus and diphtheria may experience respiratory problems and sistemic infections that leading to deathness. Infectious diseases such as tetanus and diphtheria can be prevented by immunization. These are common side effects of immunization, including swelling and pain at the injection area. The aim of this activity is give education about pain management and practice deep breathing techniques so that pain is reduced, relaxed and do not experience trauma. This community service activity uses health education methods regarding post-immunization pain management and deep breathing technique simulation involving 40 students divided into 2 classes. The result of community service activity was the increase of knowledge about pain management and lower level of pain after immunization. The recommendation school was pain measurement should be asses before and after given health education regarding pain management and continue to deliver health education about pain management to all students in elementary school. Keywords: immunization, deep breathing, pain.